THE EXISTENCE OF DRUWE CUSTOMARY LAND VIEWED FROM THE PERSPECTIVE OF NATIONAL LAND LAW - Suwanda, I Wayan (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
The function of land is not just limited to the composition of the product tools, social asset and capital asset, politics, culture, but also about values and meaningful religious. Therefore, the land is in related directly with humans that gave birth to the concept of ownership since long time ago up to now according to the customary law. The history of druwe land in the beginning is belonged to the Kingâs authority with the status of âDruwe Dalemâ and possession of the royal dignitaries such as royalty and the retainer with the ownership right status of âDruwe Jabaâ. In Lombok, such as in Mataram and West Lombok until now its existence is still recognized by the people of Balinese people that are hereditary lived in Lombok. Authors interested in highlighting the existence of customary law as the basis of the land law provisions in Indonesia. When examined customary law that grow in Indonesia have diversity (pluralism of law). This will affect the color and resolution of various land cases in the country. There are a few theories that I use such as Emile Durkheim, that determine the law as the social morality, then Ehrlich introduce the types called Entscheidungnormen (norms of decision), and the theory of legal protection for the people by Philip M Hadjon. The approach used is a conceptual approach, and statute approach Keywords: Indigenous, Land of Druwe